Reliability, Validity and Factor Structure of Fitrah Scale - Husain, Akbar; Nazam, Fauzia; Gull, Mubashir (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
Fitrah, in Islamic psychology, refers to the innate disposition or natural state with which humans are created. This concept encompasses the inherent qualities of purity, morality, and the instinctive inclination towards faith in God. Understanding and measuring fitrah is crucial as it plays a significant role in shaping individual behaviors and overall well-being. Despite its importance, there has been a lack of standardized tools to assess fitrah comprehensively. This study aims to standardize a self-report measure of fitrah with a theoretical and empirical foundation applicable to a diverse Muslim population across various contexts and rooted in the behavioral psychological tradition. The article described the development and preliminary psychometric properties (i.e., reliability and validity) of the Fitrah Scale, an 18-item measurement with a 5-factor structure comprising Beatitude, Moral Uprightness, Devoutness, Innate Goodness, and Faith in God. The Fitrah Scale has shown good content, factorial validity, and internal consistency reliability (i.e., Cronbach’s alpha).